2006
DOI: 10.1007/s10672-006-9023-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards Employee Wellness: Rethinking Bullying Paradoxes and Masks

Abstract: Wellness in organizations" should focus on the well being of individual workers. At a time when the wellness of individuals is increasingly being threatened in our workplaces, I argue that one way wellness can be sought is through careful examination of routine organizational practices. To make this point, I look to the problem of bullying in organizations and, in particular, traditional organizational responses to bullying. The paradoxes of protective legislation and protective workplace policies are explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 31 publications
0
32
0
5
Order By: Relevance
“…In recent decades there has been growing interest in understanding hostile and harmful workplace behaviours such as bullying (Hutchinson et al 2006a;O'Moore et al 2003;Vickers 2006). There is considerable evidence that bullying involves repeated, demeaning or destructive acts resulting in harm to both individuals and institutions (Simpson and Employ Respons Rights J…”
Section: Bullying At Workmentioning
confidence: 99%
“…In recent decades there has been growing interest in understanding hostile and harmful workplace behaviours such as bullying (Hutchinson et al 2006a;O'Moore et al 2003;Vickers 2006). There is considerable evidence that bullying involves repeated, demeaning or destructive acts resulting in harm to both individuals and institutions (Simpson and Employ Respons Rights J…”
Section: Bullying At Workmentioning
confidence: 99%
“…Several researchers suggested that bullying might go unnoticed and underreported in organizations where their culture tolerate and normalize such behavior (Rhod, Pullen, Vickers, Clegg, & Pitsis, 2010;Vickers, 2006;Hodson, Roscigno, & Lopez, 2006). Therefore, organizations should develop bullying prevention policies that communicate to employees that bullying is unacceptable and it will not be tolerated.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Taikant juos organizacijoje remiamasi prielaida, kad darbuotojo gerovė organizacijoje yra tiesiog individo gerovė organizacijos kontekste, t. y. pasitenkinimas tuo, kas vyksta darbo dienos metu (Vickers, 2006). Pripažįstant, kad asmuo yra nedaloma visuma ir jo gerovę darbe didele dalimi lemia asmens gerovė apskritai, visgi reikia atkreipti dėmesį į tai, kad specifinis organizacijos kontekstas gali sudaryti skirtingas sąlygas asmeniui realizuoti turimą gerovės potencialą.…”
Section: Pozityvių Psichologinių Bei Socialinių Veiksnių Stiprinančiunclassified